Phosphorescence Tuning through Heavy Atom Placement in Unsymmetrical Difluoroboron beta-Diketonate Materials - ALTUN, ZİKRİ (WILEY-V C H VERLAG GMBH, 2018)
Difluoroboron beta-diketonates (BF(2)bdks) show both fluorescence (F) and room-temperature phosphorescence (RTP) when confined to a rigid matrix, such as poly(lactic acid). These materials have been utilized as optical oxygen sensors (e.g., in tumors, wounds, and cells). Spectral features include charge transfer (CT) from the major aromatic donor to the dioxaborine acceptor. A series of naphthyl-phenyl dyes (BF(2)nbm) (1-6) were prepared to test heavy-atom placement effects. The BF(2)nbm dye (1) was substituted with Br on naphthyl (2), phenyl (3), or both rings (4) to tailor the fluorescence/phosphorescence ratio and RTP lifetimeimportant features for designing O-2 sensing dyes by means of the heavy atom effect. Computational studies identify the naphthyl ring as the major donor. Thus, Br substitution on the naphthyl ring produced greater effects on the optical properties, such as increased RTP intensity and decreased RTP lifetime compared to phenyl substitution. However, for electron-donating piperidyl-phenyl dyes (5), the phenyl aromatic is the major donor. As a result, Br substitution on the naphthyl ring (6) did not alter the optical properties significantly. Experimental data and computational modeling show the importance of Br position. The S-1 and T-1 states are described by two singly occupied MOs (SOMOs). When both of these SOMOs have substantial amplitude on the heavy atom, passage from S-1 to T-1 and emission from T-1 to S-0 are both favored. This shortens the excited-state lifetimes and enhances phosphorescence.
Keywords: boron complexes; charge transfer; heavy atom; oxygen sensing; phosphorescence; INTRAMOLECULAR CHARGE-TRANSFER; ROOM-TEMPERATURE PHOSPHORESCENCE; ACTIVATED DELAYED FLUORESCENCE; AGGREGATION-INDUCED EMISSION; MOLECULAR-ORBITAL METHODS; DIBENZOYLMETHANE-POLYLACTIDE; TUMOR HYPOXIA; MECHANOCHROMIC LUMINESCENCE; EXCITED-STATES; IN-VIVO